Seizing opportunities: MOOC takers making time for change - Deacon, Andrew; Walji, Sukaina; Jawitz, Jeff; Small, Janet; Jaffer, Tasneem (Critical Studies in Teaching and Learning, 2023)
We interviewed people living in African countries who have taken Massive Open Online Courses (MOOCs) created by the University of Cape Town to ask about their challenges, goals, and value studying online. They are drawn to taking MOOCs in part because of the claims around flexible learning opportunities for people with busy lives. A striking feature in these interviews is the many references to the challenges associated with negotiating time to study online. Here we wish to move beyond simply identifying deficit models of time or time management and rather seek to understand the value of MOOCs to people with work or career transition goals. The MOOC takers' experiences are quite different to those in conventional degree courses as MOOC participation is voluntary and must be negotiated around existing commitments, suggesting a need for reframing of what is valued by people studying online in their own time.